2014
DOI: 10.3232/sjss.2013.v3.n2.02
|View full text |Cite
|
Sign up to set email alerts
|

A micromorphological evaluation of pedogenesis on Isla Santa Cruz (Galápagos) .

Abstract: Thin sections of about 200 horizons or layers, representing 60 soil profiles in the coastal area and on the windward slopes of Isla Santa Cruz (Galápagos Islands) were analysed. Based on the fabric and the composition of the groundmass and the presence of pedofeatures in individual layers or horizons, clusters of similar material are made and 7 units and 3 subunits distinguished. Plotting these units on a survey map gives a good insight in the spatial distribution of soil materials, expressing different combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In Dystrandepts from an area north of Bellavista (Eswaran et al, 1973), and in a Hapludoll sampled near that village (Morrás, 1974(Morrás, , 1976, gibbsite occurs in part as coatings and infillings of vesicles in volcanic rocks, and as derived spherical aggregates, interpreted as having formed by transformation of a zeolite precursor (Eswaran et al, 1973) or of an amorphous gel phase (Morrás, 1974(Morrás, , 1976. In the Hapludoll profile, gibbsite also occurs as alteration product of plagioclase, again with amorphous gels as presumed intermediate phase (Morrás, 1974(Morrás, , 1976 see also Stoops, 2013). Based on the nature of these gibbsite features, there is no reason to assume that their development involved a bayerite stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Dystrandepts from an area north of Bellavista (Eswaran et al, 1973), and in a Hapludoll sampled near that village (Morrás, 1974(Morrás, , 1976, gibbsite occurs in part as coatings and infillings of vesicles in volcanic rocks, and as derived spherical aggregates, interpreted as having formed by transformation of a zeolite precursor (Eswaran et al, 1973) or of an amorphous gel phase (Morrás, 1974(Morrás, , 1976. In the Hapludoll profile, gibbsite also occurs as alteration product of plagioclase, again with amorphous gels as presumed intermediate phase (Morrás, 1974(Morrás, , 1976 see also Stoops, 2013). Based on the nature of these gibbsite features, there is no reason to assume that their development involved a bayerite stage.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case for gibbsite that, together with kaolinite, forms the main constituent of the clay fraction of a Dystrandept studied by Adelinet et al (2008), despite its proximity to the profile identified as bayeritebearing by the present study. In other soils of Santa Cruz, gibbsite is only a minor component of the clay fraction, in association with amorphous material (Stoops, 1972), with halloysite and allophane (Morrás, 1977), or with kaolinite (Candra et al, 2021), and the mineral has also been detected by XRD analysis of bulk samples (Gerbazek et al, 2023). However, these various gibbsite mentions mainly indicate that conditions for gibbsite formation by strong alteration of volcanic parent materials are met in parts of Santa Cruz, in settings that are unrelated to that of the bayerite-bearing shallow profile of the Santa Rosa area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topography is another influential factor in climate modulation, which gives rise to three main microclimates or climatic zones: the dry lowlands (arid zone), the transition zones, and the humid highlands [62]. Precipitation ranges from an annual average of 100 to 300 mm of rain in the arid zones [63] and from 1500 to more than 2000 mm of rain in the humid zones, according to records from Santa Cruz and San Cristobal [64,65].…”
Section: Geographical Contextmentioning
confidence: 99%
“…Systematic information on (top)soil properties in Galápagos is still scarce, and most of the available baseline information is drawn from a geo-pedological mission in 1962 (Stoops, 2013;Taboada et al, 2016;Rial et al, 2017) with very few additional later studies (e.g., Adelinet et al, 2008). In 2016 and 2017, three soil scientific expeditions laid the foundation for further, more detailed investigations, and the present study forms part of these ongoing research efforts carried out by the University of Natural Resources and Life Sciences Vienna in cooperation with the Galápagos National Park Directorate and other partner institutions.…”
Section: Introductionmentioning
confidence: 99%